Crustal‐scale degassing due to magma system destabilization and magma‐gas decoupling at Soufrière Hills Volcano, Montserrat. (30th August 2015) - Christopher, T. E.; Blundy, J.; Cashman, K.; Cole, P.; Edmonds, M.; Smith, P. J.; Sparks, R. S. J.; Stinton, A.
Abstract Activity since 1995 at Soufrière Hills Volcano (SHV), Montserrat has alternated between andesite lava extrusion and quiescence, which are well correlated with seismicity and ground deformation cycles. Large variations in SO2 flux do not correlate with these alternations, but high and low HCl/SO2 characterize lava dome extrusion and quiescent periods respectively. Since lava extrusion ceased (February 2010) steady SO2 emissions have continued at an average rate of 374 tonnes/day (± 140 t/d), and incandescent fumaroles (temperatures up to 610oC) on the dome have not changed position or cooled. Occasional short bursts (over several hours) of higher (∼ 10x) SO2 flux have been accompanied by swarms of volcano‐tectonic earthquakes. Strain data from these bursts indicate activation of the magma system to depths up to 10 km. SO2 emissions since 1995 greatly exceed the amounts that could be derived from 1.1 km3 of erupted andesite, and indicating extensive partitioning of sulfur into a vapour phase, as well as efficient decoupling and outgassing of sulfur‐rich gases from the magma. These observations are consistent with a vertically extensive, crustal magmatic mush beneath SHV. Three states of the magmatic system are postulated to control degassing. During dormant periods (103 to 104 years) magmatic vapour and melts separate as layers from the mush and decouple from each other. In periods of unrest (years) without eruption, melt and fluid layers become unstable, ascend and can amalgamate. Major destabilization of the mush system leads to eruption, characterized by magma mixing and release of volatiles with different ages, compositions and sources.